2020
DOI: 10.1177/0741713620927348
|View full text |Cite
|
Sign up to set email alerts
|

Does Participation in Adult Education Increase Volunteering? An Analysis of British Longitudinal Data

Abstract: High-quality longitudinal data from the UK Household Longitudinal Study gives us the opportunity to investigate whether participation in adult education (AE) fosters volunteering, and whether this depends on the volume of AE, its content, or on the qualification obtained with it. From a public enlightenment perspective, we would only expect to find an effect if the content of AE relates to social issues and domains relevant for volunteering. Yet theories emphasizing AE as a place of encounter and an activity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
8
0
2
Order By: Relevance
“…The study results show that the educational status of healthy volunteers affect the intention to improve their performance [19]. The educational level significantly and positively impacts the social interaction and self-perception of health cadres [20]. Government employees Int J Public Health Sci ISSN: 2252-8806  Knowledge, motivation, attitude, job design and health cadre performance: … (Rinayati) 387 engage significantly more in volunteering than their counterparts in the private sector.…”
Section: The Characteristics Of Respondentsmentioning
confidence: 93%
“…The study results show that the educational status of healthy volunteers affect the intention to improve their performance [19]. The educational level significantly and positively impacts the social interaction and self-perception of health cadres [20]. Government employees Int J Public Health Sci ISSN: 2252-8806  Knowledge, motivation, attitude, job design and health cadre performance: … (Rinayati) 387 engage significantly more in volunteering than their counterparts in the private sector.…”
Section: The Characteristics Of Respondentsmentioning
confidence: 93%
“…All these activities can foster social bonding and extend one's social network. A recent study by Rüber and Janmaat (2021) shows that participation in adult education increases volunteering, irrespective of volume, content and obtained qualifications. The authors argue that the effect may be driven by the social interactions and self-perceptions gained through participation in AET.…”
Section: Social Network Effectsmentioning
confidence: 99%
“…On a social level, individual health-related behaviour is influenced in particular by peers, a marital relationship or community ties (Umberson et al 2010a, p. 142). Community ties can be strengthened, as has been shown for the case of civic or cultural participation, through participation in AET (Rüber and Janmaat 2021;Ruhose et al 2019). Although the literature suggests that increasing social networks have a positive effect on health behaviour, there are also conditions under which contact with other people can have negative effects on one's health behaviour.…”
Section: Social Network Effectsmentioning
confidence: 99%
“…This path (adult learning influences low-level personality traits that then increase likelihood of volunteerism) was generalized to all adult learning and is the path this study modeled. Rüber and Janmaat (2021) used longitudinal data from the United Kingdom to test components of Rüber et al's (2018) model. Their results showed that participation in adult education raised volunteerism by nearly four percent.…”
Section: Civic Participation and Adultmentioning
confidence: 99%